2022
DOI: 10.1111/ctr.14785
|View full text |Cite
|
Sign up to set email alerts
|

Levels of donor‐derived cell‐free DNA and chemokines in BK polyomavirus‐associated nephropathy

Abstract: Background: BK polyomavirus-associated nephropathy (BKPyVAN) carries a risk of irreversible allograft injury. While detection of BK viremia and biopsy assessment are the current diagnostic gold standard, the diagnostic value of biomarkers reflecting tissue injury (donor-derived cell-free DNA [dd-cfDNA]) or immune activation (C-X-C motif chemokine ligand [CXCL]9 and CXCL10) remains poorly defined. Methods: For this retrospective study, 19 cases of BKPyVAN were selected from the Vienna transplant cohort (biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…Aside from immunologic rejection, there can be various triggers for the release of dd-cfDNA and chemokines, such as polyomavirus nephropathy, urinary tract infection, and acute renal failure. 20,35,42 None of the study participants had BK or JC viremia, and only 1 developed moderate acute renal failure due to diarrhea, but this event was not associated with any of the time points, wherein biomarker testing was performed. During the trial, 10 episodes of lower urinary tract infection were recorded, and, in addition, 1 had pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from immunologic rejection, there can be various triggers for the release of dd-cfDNA and chemokines, such as polyomavirus nephropathy, urinary tract infection, and acute renal failure. 20,35,42 None of the study participants had BK or JC viremia, and only 1 developed moderate acute renal failure due to diarrhea, but this event was not associated with any of the time points, wherein biomarker testing was performed. During the trial, 10 episodes of lower urinary tract infection were recorded, and, in addition, 1 had pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have generalized that patients with higher dd-cfDNA experience higher rates of rejection, the ability to accurately predict adverse events among these patients is still lacking (97). This is because dd-cfDNA is elevated in a multitude of pathologies and lacks the ability to distinguish among infectious or immunologic etiologies of graft injury (98). In fact, some studies suggest that among low-risk kidney transplant recipients, the benefit provided from early dd-cfDNA monitoring may only be marginally better than current clinical management (99).…”
Section: Ready For Prime Timementioning
confidence: 99%
“…Kant et al suggested that GcfDNA may be a useful noninvasive test to assess progression of BKPyV to BKPyVAN (14). BKPyVAN can induce moderate increases in GcfDNA (15). Goussous et al suggested that elevations in GcfDNA are not specific to kidney allograft rejection and can be associated with BK viremia affecting the transplanted kidney (16).…”
Section: Introductionmentioning
confidence: 99%
“…suggested that GcfDNA may be a useful noninvasive test to assess progression of BKPyV to BKPyVAN ( 14 ). BKPyVAN can induce moderate increases in GcfDNA ( 15 ). Goussous et al.…”
Section: Introductionmentioning
confidence: 99%